The Role of Leadership in Bureaucracy Reform - Muslim, Muh Azis; Hariyati, Desy (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2013)
Leadership refers to one’s capacity to change another party’s behavior as he wishes. Regional leadership has significant influence to build a better quality regional bureaucracy. Bureaucracy reform is a demand that needs to be met to improve bureaucracy’s quality and performance which from time totime suffers stigma from the public. This research applies qualitative datacollection through in-depth interview with local government, parliament (DPRD), NGO, business people, and public leaders. The result in general indicates that HerryZudianto’s leadership role as seen from Mintzberg theory has been performed well, particularly as seen from dimension of interpersonal roles, informational roles, and decisional roles.